THE CRIMINAL PROVISIONS OF DATA PRIVACY LAW AND ANATOMY OF CYBERCRIME LAW IN INDONESIA - Awaludin Marwan; Amalia Syauket; Andi Tri Haryono (ADISAM Publisher, 2025)
This paper will discuss the criminal provisions of data privacy law and anatomy of cybercrime law in Indonesia before the amendment of ICT Law and its implementation. During pandemic time, cyber incidents have increased over time. Indeed, cybercrime law in Indonesia regulates prohibition of hacking, phishing, illegal interception, carding, pornography, defamation and so on in accordance with the Electronic Information and Transactions Act (Undang- Undang Informasi dan Transaksi Elektronik, UU-ITE hereinafter also referred to as ‘Indonesia ICT Law), Law No. 11 of 2008 which later on revised into Law No. 19 of 2016 and currently became Law No. 1 of 2024. At the same time, Law No. 27 of 2022 (Personal Data Protection/ PDP Law) concerning data privacy protection also stipulated criminal provision and already used in case law. This law can be a part of cybercrime law system in Indonesia side by side with Indonesia ICT Law. Back to Indonesia ICT Law, the implementation of this law can be seen in 210 case law which I have collected and analysed in this paper. I have found that cases are dominated by online defamation, hate speech on social media, pornography, and extortion. Meanwhile, these cases are relatively similar with ‘ordinary crime’ which is regulated in criminal code. The high technological crimes such as hacking, phishing, illegal interception, carding, are less shown, hereby. The highest case number is online defamation which it was also triggered by some human rights activists sued to judicial review through the constitutional court to eliminate the article concerning online defamation. The reason of judicial review concerning online defamation is because this article may potentially oppress the freedom expression, freedom of speech, and freedom of press. The anatomy of cybercrime law in Indonesia still remains some problems in legal norms and legal practice.